The relationship between head-neck ratio and pseudotumour formation in metal-on-metal resurfacing arthroplasty of the hip. - Grammatopoulos, G; Pandit, H; Murray, D; Gill, H (2010)
Pseudotumour is a rare but important complication of metal-on-metal hip resurfacing that occurs much more commonly in women than in men. We examined the relationship between head-neck ratio (HNR) and pseudotumour formation in 18 resurfaced hips (18 patients) revised for pseudotumour and 42 asymptomatic control resurfaced hips (42 patients). Patients in whom pseudotumour formation had occurred had higher pre-operative HNR than the control patients (mean 1.37 (sd 0.10) vs mean 1.30 (sd 0.08) p = 0.001). At operation the patients with pseudotumours had a greater reduction in the size of their femoral heads (p = 0.035) and subsequently had greater neck narrowing (mean 10.1% (sd 7.2) vs mean 3.8% (sd 3.2) p < 0.001). No female patient with a pre-operative HNR ≤ 1.3 developed a pseudotumour. We suggest that reducing the size of the femoral head, made possible by a high pre-operative HNR, increases the risk of impingement and edge loading, and may contribute to high wear and pseudotumour formation. As the incidence of pseudotumour is low in men, it appears safe to perform resurfacing in men. However, this study suggests that it is also reasonable to resurface in women with a pre-operative HNR ≤ 1.3.